Vitamin B12 deficiency and its impact on healthcare: a population-level analysis and call for action - de Carvalho, Leonardo P.; Akamine, Nelson; Di Pietro, Marcelo S.; França, Carolina Nunes; Oliveira, Rodrigo; Lopes, Renato D. (Frontiers in Nutrition, 2026)
IntroductionVitamin B12 deficiency is a growing health concern, affecting millions worldwide. This study aims to evaluate the pattern of vitamin B12 deficiency in a large healthcare system and assess its impact on hospitalizations and associated diseases.MethodsVitamin B12 test results were retrospectively collected from administrative datasets of Brazil’s public and private healthcare systems between 2016 and 2023. Data from health campaigns measuring vitamin B12 levels across the country were used to calculate the percentage of abnormal test results. The Mann-Kendall test was applied to assess trends in hospitalizations over time, while the Pearson correlation test was used to evaluate the association between vitamin B12 deficiency and other hospitalization causes.ResultsA total of 84 million vitamin B12 measurements were analyzed, revealing a 12-fold increase in tests performed, rising from two million to 25 million over the study period. Of these, 35 million measurements were from the public and 47·8 million from private healthcare system. The trend of hospitalizations associated with vitamin B12 deficiency increased by 32% over the study period (p < 0·05). Hospitalizations associated with vitamin B12 deficiency were correlated with other B vitamin deficiencies (B1 and B6), as well as hospitalizations due to cardiovascular, hematological, neurological, psychological, and gastrointestinal diseases.DiscussionThis population-based study highlights a progressive increase in vitamin B12 deficiency-related hospitalizations, suggesting a previously underrecognized public health burden. Additionally, these findings underscore the correlation between vitamin B12 deficiency, other B vitamin deficiencies, and relevant clinical diseases.